(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The theory of forensic science has long been supplemented by additional classifications, which differed in certain criteria and comprehensively reflected the essence of forensic science and expert research. The issue of forensic examinations classification in Ukraine according to the criteria existing in the doctrine and normative legal acts has been considered. The purpose of the study is the correct classification of historical and archaeological examination in the system of forensic science of Ukraine, to determine the main aspects and criteria for the classification of forensic science in Ukraine. To solve this goal, the scientific literature and regulatory support on the topic have been analyzed. It has been concluded that the historical and archaeological examination does not belong to the already existing types, as it has a unique subject, object and methods. It can be classified according to various criteria presented in the article. Certain changes and transformations in the classifications of forensic examinations occur as a result of the emergence of a new type or kind of forensic examination, new objects and tasks of research. The development of a particular type of expertise can contribute to the formation of a new class. The most common is classification according to the field of special knowledge by types and subtypes, enshrined in the Instruction on the appointment and conduct of forensic examinations and expert research, approved by the Order of the Ministry of Justice of Ukraine. Historical and archaeological examination as a new type, which is currently in the process of formation and development, requires proper classification in expertise. Classifications are diverse depending on the criteria and have not only theoretical but also practical significance, allow to avoid errors in the appointment of forensic examinations and expert research, which, in turn, speeds up the study.